Assessment of Lipid Profile among Women with Malignant and Non-malignant Breast Lesions in a Tertiary Hospital, Nigeria: A Pilot Study - Ajeigbe AK; Omisore AD; Akinde AO; Makinde RA; Ajose OA (Ibom Medical Journal)
Context: Breast cancer (BC) is the most common cancer in women. Reports suggest a possible relationship between lipids and BC; but the pattern of lipid profile in breast lesions is unknown.